ORGANISASI SOSIAL KEAGAMAAN: PERSYARIKATAN MUHAMMADIYAH, TOKOH, DAN KEGIATANNYA DI BIDANG PENDIDIKAN - Suhartini Khalik; Bahaking Rama; Andi Achruh (CV. ADIBA AISHA AMIRA, 2024)
This research aims to describe the religious organization of Persyarikatan Muhammadiyah, its leaders, and its activities in the field of education. This research utilizes qualitative methods. The data analysis technique employed is literature review. The research data is obtained from relevant readings related to the research topic. The research process involves collecting various sources of study such as journals, books, newspapers or magazines, and internet articles that are relevant to this research. After studying and examining these sources, conclusions are drawn from the research. The results of the research indicate that Muhammadiyah has made significant contributions to education in the country, as evidenced by its role in the field of education from before the independence era until the present. This can be seen from the numerous educational institutions established by Muhammadiyah, ranging from primary education to higher education.